EFL Students' Experiences of Using ChatGPT in Creative Writing: A Qualitative Case Study at an Islamic Boarding School in Tasikmalaya - Risna Amelia; Dedeh Rohayati; Wawan Tarwana (Journal of English Education Program (JEEP), 2026)
This study explores the experiences of EFL students in using ChatGPT to support their writing skills, specifically in the form of dialogue scriptwriting. This study used a qualitative method with the type of case study. The data were obtained through observation, document analysis, and interviews which were administered to six tenth-grade students of a senior high school integrated Islamic boarding school in Tasikmalaya where the use of mobile is restricted. The students were selected through purposive sampling. The findings reveal that ChatGPT serves as a valuable tool to supports students in refining and editing their written work. However, overreliance on the tool may hinder the development of students’ critical thinking and independent writing skills. Based on these findings, it is recommended that teachers guide students in using ChatGPT as a supplementary tool rather than a primary source, and discussions about the ethical use of ChatGPT can also foster more responsible and effective learning experiences.